Women's Perceptions about Breastfeeding: A Preliminary Study - Cecilia Obeng; Stephanie Dickinson; Lilian Golzarri-Arroyo (MDPI AG, 2020)
Background: Breastfeeding rates are low in many communities in the United States and require attention to come up with ideas that will help increase breastfeeding. This study investigated the effects of income, age, race and education on mothers' perceptions about breastfeeding and whose needs and views should be considered in a women's breastfeeding journey. Methods: A survey was distributed via email and Facebook to 525 participants; 453 participants (86.3%) responded to the survey. Results: Younger adults were more likely to agree that fathers should have some say about breastfeeding. Those earning USD 0-USD 50,000 were more likely to agree relative to those with higher incomes on children being entitled to mother's milk, and children's needs over-riding those of others. There was a statistically significant difference by education about women's wishes about breastfeeding being considered more important than those of their spouses. However, there was no statistically significant difference for any demographic group for breastfeeding decisions coming from women only. On women's breasts being primarily for infant's nutrition, people who earned USD 0-USD 50,000 were more likely to agree relative to those who earned more than USD 50,000; younger adults were significantly more likely to agree. Those who earned USD 0-USD 50,000 were more likely to agree relative to those in other income brackets that extended family members should have input regarding babies being breastfed; minority participants were significantly more likely to agree relative to white participants; those with less than 4-year college education were more likely to agree relative to those with a minimum of four-year college education. Younger adults were more likely to agree that employers must provide extended maternity leave to make it easier for mothers to breastfeed. On women having the right to breastfeed in public places, younger adults were significantly more likely to agree compared to older adults. Conclusion: Women have favorable views about breastfeeding and prefer being in charge about decisions to breastfeed.